Effects of Baicalin on piglet monocytes involving PKC–MAPK signaling pathways induced by Haemophilus parasuis - Chun Ye (BMC Veterinary Research, 2019)
Abstract Background Haemophilus parasuis (HPS) is the causative agent of Glässer’s disease, characterized by arthritis, fibrinous polyserositis and meningitis, and resulting in worldwide economic losses in the swine industry. Baicalin (BA), a commonly used traditional Chinese medication, has been shown to possess a series of activities, such as anti-bacterial, anti-viral, anti-tumor, anti-oxidant and anti-inflammatory activities. However, whether BA has anti-apoptotic effects following HPS infection is unclear. Here, we investigated the anti-apoptotic effects and mechanisms of BA in HPS-induced apoptosis via the protein kinase C (PKC)–mitogen-activated protein kinase (MAPK) pathway in piglet’s mononuclear phagocytes (PMNP). Results Our data demonstrated that HPS could induce reactive oxygen species (ROS) production, arrest the cell cycle and promote apoptosis via the PKC–MAPK signaling pathway in PMNP. Moreover, when BA was administered, we observed a reduction in ROS production, suppression of cleavage of caspase-3 in inducing apoptosis, and inhibition of activation of the PKC–MAPK signaling pathway for down-regulating p-JNK, p-p38, p-ERK, p-PKC-α and PKC-δ in PMNP triggered by HPS. Conclusions Our data strongly suggest that BA can reverse the apoptosis initiated by HPS through regulating the PKC–MAPK signaling pathway, which represents a promising therapeutic agent in the treatment of HPS infection.